Auditoría de gestión y sus efectos en la operatividad financiera de la empresa agrícola “Angueta Hinojosa Guido Wilfrido”, del cantón La Maná año 2016-2017 - Crespo Ávila, Digna Isabel (2018)
The agricultural company Angueta Hinojosa Guido Wilfrido, dedicated to the production and commercialization of banana boxes, located in the Canton La Maná, Av. 19 de Mayo and Segundo Estrella, starts its commercial and productive activities on June 06, 2007. The present The aim of this research work is to evaluate the impact of the management audit and its effects on the financial operation of the Angueta Hinojosa Guido Wilfrido Agricultural from the 2016-2017 period. It was based on descriptive, exploratory and explanatory research in which the degree of efficiency and effectiveness in which the operational management of the company is developed was determined; In addition, deductive, inductive and historical methods were used with events that occurred in agriculture. The necessary instruments were used to collect the information, such as questionnaires, observation guides, work papers, risk matrix, checklist, file review, etc. In the evaluation of internal control in the purchasing, sales and accounting department through the COSO II, an acceptable level of risk was obtained in the management audit, in the evaluation of the operational management of the processes performed, an effectiveness was determined Deficient in the management regarding the fulfillment of the mission, vision and objectives of the agricultural due to the lack of control over the economic resources, financial indexes were applied that allowed to know the financial situation that the company Agricola Angueta Hinojosa Guido Wilfrido is going through. As recommendations, you must implement a more detailed organizational structure, update the functions manual, implement an internal control system in all departments, apply management audits and monitor the results, improve the management of costs and expenses to obtain an Greater utility, constantly assess the levels of effectiveness, efficiency and economy, for the analysis of management indicators and decision making. Keywords: audit, management, financial operability